Barriers to entry and the self-regulating profession: Evidence from the market for Italian accountants - Bernardo Bortolotti; Gianluca Fiorentini (Fondazione Eni Enrico Mattei (FEEM), 1997)
This paper provides a systematic study of the market for accountants in Italy during the period 1980-91. Firstly, it develops a comparison in the determinants of incomes of the two competing professions (Commercialisti and Ragionieri) focusing on entry as one of the main variables of interest to explain some stylised facts and trends in the profession itself. Second, we carry out an empirical analysis using panel data to test the effects of self-regulation, in terms of discretion in the admission policy in the profession, on incomes. Our results confirm that the institutional barrier to entry is effective in generating economic rents; furthermore, we show that admission rates are an endogenous variable strongly influenced by past level of incomes.
Keywords: J44; L44; M40; 330; Self-regulation; Professional services; Antitrust policy; Kaufmännische Berufe; Markteintritt; Italien